Faktor Faktor yang Mempengaruhi Persepsi Harga Ayam Pedaging di Pasar Tradisional Kabupaten Tolitoli - Ibrahim, Ibrahim; Yusuf, Nur Apika (Fakultas Peternakan Universitas Madako Tolitoli, 2025)
This study aims to identify the factors influencing consumer perceptions of broiler chicken prices in Susumbolan Market and Bumi Harapan Market, Tolitoli Regency. The research location was determined using purposive sampling, with a total of 35 respondents consisting of consumers/purchasers of broiler. This research employed a descriptive approach, and the data were analyzed using descriptive analysis and Spearman’s Rank Correlation. The results showed that consumer perceptions of broiler chicken prices in both markets were influenced by several independent variables, including age (X1), gender (X2), education level (X3), family dependents (X4), and income level (X5). Overall, these variables contributed to shaping consumer perceptions of broiler chicken prices. These findings highlight that consumers’ socio-economic factors are significant determinants in understanding price perceptions in traditional markets, and they can serve as a basis for developing marketing strategies and pricing policies.